2020
DOI: 10.1111/1475-6765.12396
|View full text |Cite
|
Sign up to set email alerts
|

Confident and cautious candidates: Explaining under‐representation of women in Danish municipal politics

Abstract: Why are women under‐represented even in democratic and egalitarian countries? Previous research considers either demand‐side or supply‐side explanations. We integrate both perspectives in a least‐likely case for the under‐representation of women, namely the municipal councils in Denmark. The data stems from a candidate choice conjoint experiment, a survey among potential candidates, and data on the actual pool of nominated candidates. On the voter demand‐side, we show that there is no pro‐male bias in general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 62 publications
0
19
0
4
Order By: Relevance
“…Media treatment had no impact on women's agreement with either statement (voting: p-value = 0.189; competency: p-value = 0.686). Participants in this study therefore reflect the gender bias perceptions of women in other European (Dahl and Jacob 2021;Foos and Gilardi 2020) and American (Dolan and Hansen 2018) studies. Clearly, then, women's beliefs about voter gender bias were strong even when media discrimination had not occurred, and counter-discriminatory media did not encourage women to engage in politics.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Media treatment had no impact on women's agreement with either statement (voting: p-value = 0.189; competency: p-value = 0.686). Participants in this study therefore reflect the gender bias perceptions of women in other European (Dahl and Jacob 2021;Foos and Gilardi 2020) and American (Dolan and Hansen 2018) studies. Clearly, then, women's beliefs about voter gender bias were strong even when media discrimination had not occurred, and counter-discriminatory media did not encourage women to engage in politics.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, women often have less money, which is needed to launch a campaign (Williams 2008). However, even studies considering political gender gaps at young ages in relatively gender egalitarian societies like Denmark and Germany (Dahl and Jacob 2021; Pfanzelt and Spies 2019) – where gender socialisation is less severe and before such familial and economic gender differences emerge – find that political gender gaps are significant.…”
Section: Political Ambition Gender Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on the impact of ideology or partisanship on gender bias are located in the two-party system of the US and reveal that Republican voters prefer men candidates while Democratic voters favor women politicians (see for instance Sanbonmatsu, 2002;King and Matland, 2003;Sanbonmatsu and Dolan, 2009;Schwarz and Coppock, 2022). Much less in known about the impact of partisanship on gender bias in the European context, in with the multi-party systems lend themselves for a more detailed differentiation between parties (but see Wilcox, 1991;Saha and Weeks, 2020;Dahl and Nyrup, 2021). Our experiment demonstrates that not all voters show a gender bias, only the voters from the "extreme" parties.…”
Section: Discussionmentioning
confidence: 99%
“…Wilcox (1991), analyzing Eurobarometer data, showed that right-wing voters have less confidence in women legislators than in men legislators in five out of the eight countries studied. More recently, Dahl and Nyrup (2021) conducted a candidate choice experiment showing that left-wing voters prefer women candidates, while right-wing voters show no gender bias in Denmark. By contrast, Saha and Weeks (2020) did allow more fine-grained differences among parties, and show very little impact of partisanship on gender bias in preferences of candidates in the UK.…”
Section: Theoretical Frameworkmentioning
confidence: 99%